Heterologous expression and secretion of Bacillus coagulans ST-6 xylanase in Lactococcus lactis NZ9000 - Roslan, Abdullah Munir (2017)
Xylan polymer backbone can be metabolized by xylanase enzyme. Xylanase has been widely studied for its biological function in food industry and paper pulp bleaching. Metabolising xylan using xylanase is the preferred approach as it is the easiest and cheapest method available. Xylanase has been cloned and overproduced in both Gram negative Escherichia coli and Gram positive Bacillus subtilis. Although B. subtilis and E. coli are known cell factories for expression of heterologous proteins, the production of xylanase in these hosts eventually reduces the quality of the products with the presence of impurities such as proteases and endotoxins. Therefore, the production of xylanase using Lactococcus lactis is a safer strategy to produce xylanase due to its food-grade status. This study was aimed to develop a genetically modified Lactococcus lactis NZ9000 strain harbouring a plasmid that secretes Bacillus coagulans ST-6 endoxylanase into the exterior environment. Recombinant clones developed in this study was found to successfully secrete the xylanase using its native signal peptide, L. lactis NZ9000 secreted endogenous protein, USP45 signal peptide and Pediococcus pentosaceus K1 signal peptide; SPK1. Secreted xylanase from transformant colonies was detected by the clear zone formations on remazol-brilliant-blue-xylan (RBB-xylan)-containing agar plate assay after 24 h incubation. The expression of this enzyme in the transformants was further confirmed by Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) and western immunoblotting analysis. A band size of ~20 kDa corresponding to B. coagulans ST-6 xylanase was identified in the samples of HisTagged purified protein derived from affinity chromatography of the culture media of induced recombinant clones. The use of different signal peptides showed differences in the secretion of xylanase. Signal peptide SPK1 used for L. lactis NZ9000 has higher secretion efficiency of 25.3% compared to the other two signal peptides; USP45 (19.9%) and NSP (18.2%). However, the recombinant strain using signal peptide USP45 produced and secreted the highest amount of xylanase (16.9 µg/mL) among all three strains